Organization of Experimental Technological Complex for Serial Manufacturing and Testing of Products and Semi-Products Made of Diamond-Like and Laminated Composites for Leading Branches of Mechanical Engineering - Bilous V.А.; Voyevodin V.М.; Strelnitskij, V.Ye.; Didenko, S.Yu.; Rybka О.V.; Mazilov О.V.; Vasyl’ev, V.V.; Luchaninov, ОА О.А.; Reshetnyak О.М.; Ilchenko М.І.; Kutnij, V.Ye.; Vyeryovkin А.А.; et al. (Science and Innovation, 2024)
An experimental technological complex has been created. It consists of the sections for coating with diamond-like nanostructured composites; for manufacturing the radio-protective and other types of laminated metal composites; and for testing the radio-protective characteristics of materials. The technological equipment and the tester of radio-protective properties have been upgraded. On the basis of the developed experimental methods the batch of diamond-like coated ring seals of large diameter and samples of Al-Pb laminated composites have been made. The radio-protective effectiveness of composites has been experimentally established to be 30—40 % higher than that of aluminum.